Konflikt zbrojny jako źródło kryzysu migracyjnego. Wybrane formy wsparcia uchodźców z Ukrainy - Olszewska-Łabędź , Beata (Kultura-Społeczeństwo-Edukacja, 2022)
Armed conflicts are an integral part of a globalized world. And although their frequency, intensity and duration are varied – just like the motives for their occurrence – their common elements are suffering, pain, fear and death of innocent people. The victims of armed conflicts are then forced to make efforts related to the struggle for survival, and some of them decide to migrate to safer places, even beyond the borders of their country. The article is a review, pointing to one of the sources of migration crises, which is the armed conflict. The author briefly refers to the conflicts and their consequences in recent history, focusing mainly on the current topic of aggression by the Russian Federation against Ukraine, launched on February 24, 2022. The aim of the article is to present selected forms of support to refugees from Ukraine, both by the government in Poland and non-governmental organizations.